ANALISIS KARAKTERISTIK STOMATA PADA DAUN TANAMAN BAMBU REJEKI (Dracaena reflexa) SEBAGAI TANAMAN HIAS PENYERAP POLUSI DI KAWASAN KOTA MALANG - Juma’ani; Anita Munawwaroh (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2017)
Air pollution is changes of air arrangement from its normal state that is caused by the ingress of foreign materials or substances in the air. The resulting pollutants include SO2, NO2, CO2, O3, hydrocarbons, and heavy metals such as lead (Pb), zinc (Zn) and cadmium (Cd). The impact of plant’s vehicle exhaust gas is seen from the leaf mesophyll damage especially in the palisade tissue and the reduced number of stomata. Responding to the problem, conducted research with the aim to know the influence of pollution on the amount of stomata on the plant bamboo rejeki (Dracaena reflexa) as ornamental plants absorb pollution in the area of Malang city using the method of polishing the acne (aceton). The results showed that the number of stomata in polluted areas of vehicle pollution decreased at each point compared to areas not polluted by vehicles. In the contaminated area the average number of stomata is at point one 49, the second point 42.5, and the third point 37, whereas in the area that is not contaminated with the average number of stomata at point one 60.5, the second point is 68, and the point three is 70,5. Damage or Decrease in the number of stomata occurs due to the entry of gas that is toxic through stomata with diffusion process, so that the liquid composition of the cell becomes disturbed and the cell becomes damaged and dead.